Phytochemical composition and antioxidant activities of some wild edible plants locally consumed by rural communities in northern Uganda - Nyero, Alfred; Anywar, Godwin Upoki; Achaye, Innocent; Malinga, Geoffrey Maxwell (Frontiers in Nutrition, 2023)
Background Acalypha rhomboidea, Asystacia gangetica, Crassocephalum sacrobasis, Crotalaria ochroleuca, Heterosis rotundifolia, Hibiscus cannabinus, Hibiscus sp., Hibiscus surratensis, Ipomoea eriocarpa, Maerua angolensis, Senna obtusifolia and Vigna membranacea are among the common wild edible plants in the Acholi sub-region, northern Uganda. This study evaluated the phytochemical constituents and antioxidant potential of the plants. Methods Fresh leaves collected from each plant species were air-dried under shade. The phytochemical contents of the ethanol and petroleum ether extracts were determined using standard protocols. The antioxidant content of the methanolic extracts was assessed by DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. Results Preliminary phytochemical analyses indicated the presence of tannins, reducing compounds, alkaloids, flavonoids, flavons aglycones, flavanosides, anthracenosides, anthocyanosides, volatile oils, coumarins, steroid glycosides, sterols and triterpenes. However, the extracts did not contain any emodols and saponins. The results of the quantitative phytochemical analysis showed that the contents of different phytochemicals detected varied significantly (p<0.05) among the selected plants. The amount of tannins in mg/g (gallic acid equivalent) of dry weight varied from 3.90±0.16 in C. ochroleuca to 10.41±0.78 in I. eriocarpa, total flavonoids in RE, mg/g dry matter from 4.07±0.11 in I. eriocarpa to 14.94±0.08 in S. obtusifolia. Total alkaloids in mg/100g ranged from 1.59±0.30 in I. eriocarpa to 6.37±0.24 in Hibiscus sp. Total phenolic content in GAE, mg/g dry matter ranged from 13.39±0.26 in A. rhomboidea to 64.25±0.54 in I. eriocarpa. The in vitro antioxidant assays revealed substantial free radical scavenging property in all the plants. Antioxidant activity expressed as IC50 (ppm) ranged from 13.39 for A. rhomboidea to 64.84 for I. eriocarpa, compared to 12.82 for ascorbic acid standard. The content of total phenolic compounds and total tannins had significant and positive correlations with DPPH free radical scavenging activity. Conclusions The findings of this study provide evidence that the studied species are excellent natural sources of phytochemicals and antioxidants. Hence their regular consumption could provide human health benefits by protecting against oxidative stress related diseases. Further research is needed on the structural characterization of the phytochemicals and the determination of the antimicrobial activities of the plant extracts.